Analisis Kelayakan Usaha Penangkapan Ikan Teri (Stolephorus sp.) Nelayan Tradisional di Desa Sanggalangit, Kecamatan Gerokgak, Kabupaten Buleleng, Provinsi Bali. - Putri, Ni Kadek Dwi Widyanti; Restu, I Wayan; Negara, I Ketut Wija; Wirawan, I Gede Wahyu Surya (Current Trends in Aquatic Science; Vol 4 No 1 (2021), 2021)
Sanggalangit is one of the villages in Gerokgak District, Buleleng Regency, Bali Province. This village located at the coastal area. The main catch of fishermen in there is anchovy (Stolephorus sp.). The feasibility analysis of anchovy fishing business by traditional fishermen in Sanggalangit aims to determine the condition of the fishing business and analyze the feasibility of anchovy fishing business in Sanggalangit. This research took place from December 2019 to January 2020. Primary data were obtained by interview and direct observation in the field. Sampling was done by purposive sampling for 30 times fish landing (30 trips). Based on the data obtained, the fishing business classified as small scale (traditional) with a profit sharing system. Profit sharing system were 50% for owner's fishermen and 50% for working fishermen. Investment costs incurred in the amount of Rp. 58,200,000. The fixed cost per trip is Rp. 70,529 and the average variable cost per trip is Rp. 425,708. Average revenue per trip Rp. 706,417 with a profit Rp. 210,179. The value of the Production BEP is 2,156 kg and the Sales BEP is Rp 37,275,815 in a  year. Analysis of R /C Ratio obtained a value of 1.42 shows that the business is feasible to run and can provide benefits. Payback Period value 1.32 shows that the category of initial capital return is relatively fast.